“Ingsun” Misteri Tasawuf Mistik Syekh Siti Jenar - Aris Fauzan (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
The mysticism up to now has been a debatable discourse. The notion and practice to fuse “the self” to “the Creator” understood in so many meanings is an interesting study. No exception the issue also falls on the concept of “Ingsun” or the I-amness solidified by Syekh Siti Jenar. The study is deeply aimed to re-reveal the notion and practice of the prominent figure. According to the writer, the teaching of Ingsun makes serious effort to turn a human consciousness back to authenticity especially in relation to religion. Ingsun opens the awareness that everybody has to actually receive the life always forming a pair among goodnessbadness, life-death and God-servant. Goodness, life and God are the eternal realities of the God. While badness, death and servant are the human realities. Meanwhile the teaching of Ingsun acts as brigde for a gap between human and God. Keywords: Ingsun, The Ultimate Reality, Anthrophocentrism, Syekh Siti Jenar